Incorporación de música en el proceso de ordeñe en vacas lecheras de un tambo de la Universidad Nacional de Asunción, Paraguay - Lara, Marta (2024)
The effect of Guarania genre music on productive performance and animal well- being (milk production and serum cortisol) was evaluated. In total, 17 animals of various breeds and in different stages of lactation were used, with a crossover design, where each animal received both treatments in each period (inclusion and non-inclusion of music in the milking process). Each period was two weeks. Daily controls of milk production were carried out (two milkings per day) and blood samples were obtained weekly to determine serum cortisol concentrations. The average milk production of the group of cows without music application was 19.7 L/day and in the group of cows with music application it was 20.4 L (p=0.008). 96% of cortisol concentrations had a level less than 1 µg/dl, considered within the reference range, and without significant difference between treatments.